The Derivational and Compounding Process in William Shakespeare’s Literary Works - Rosalia Revita Cahyani; Sara Immaculata Terra Istinara; Agnes Chika Damayanti; Kurniadining Sri Pertiwi (Yayasan Karinosseff Muda Indonesia, 2020)
One importance of studying morphology in literary work is increase the vocabulary. Perhaps the biggest contributions to the English language of Shakespeare may be the addition of new words and phrases that have transformed the language and make it more vivid and descriptive. Shakespeare also changing nouns into verbs, verbs into adjectives, connecting words never used together, adding affixes, and devising words wholly original. This study aims to know how the words are formed through derivational and compounding process. In this paper, we take the data from some of William Shakespeare’s works. We use qualitative method by using morphological approach to analyze the data. Morphological approach focused on the identification and interpretation of the meaning of the words and the analysis of the morphemes attached to the words. We collect the data by downloading 11 of William Shakespeare's works, reading the words, selecting the data, and summarizing the data. Then, it’s followed by describing and determining the function of the morphemes and analyzing the change of the word class as techniques of analyzing the data. The result of this study shows that for derivational process, affix -ish , -y , -less , -ate , -eous , fore- , pur- , fore- , -y , and un- as adjectivalizer, affix -ify , en- , un- , and fore- as verbalizer, and affix -er , -y , and -ment , as nominalizer. For compounding process, we found there are two types of compound word : hyphenated compound and closed compound.